The role of neuroinflammation in neurodegenerative diseases: current understanding and future therapeutic targets - Adamu, Alhamdu; Li, Shuo; Gao, Fankai; Xue, Guofang (Frontiers in Aging Neuroscience, 2024)
Neuroinflammation refers to a highly complicated reaction of the central nervous system (CNS) to certain stimuli such as trauma, infection, and neurodegenerative diseases. This is a cellular immune response whereby glial cells are activated, inflammatory mediators are liberated and reactive oxygen and nitrogen species are synthesized. Neuroinflammation is a key process that helps protect the brain from pathogens, but inappropriate, or protracted inflammation yields pathological states such as Parkinson’s disease, Alzheimer’s, Multiple Sclerosis, and other neurodegenerative disorders that showcase various pathways of neurodegeneration distributed in various parts of the CNS. This review reveals the major neuroinflammatory signaling pathways associated with neurodegeneration. Additionally, it explores promising therapeutic avenues, such as stem cell therapy, genetic intervention, and nanoparticles, aiming to regulate neuroinflammation and potentially impede or decelerate the advancement of these conditions. A comprehensive understanding of the intricate connection between neuroinflammation and these diseases is pivotal for the development of future treatment strategies that can alleviate the burden imposed by these devastating disorders.